Islamic Religious Education and the Sustainable Development Goals: A Critical Analysis of the Theory-Practice Nexus - Andi Taufik; Ahmad Sukandar (CV. Media Digital Publikasi Indonesia, 2026)
This study undertakes a critical analysis of the theoretical frameworks underpinning the relationship between Islamic Religious Education (PAI) and the Sustainable Development Goals (SDGs). It identifies significant gaps between normative theological discourse and empirical implementation in educational settings. Employing a systematic literature review (SLR) with qualitative-interpretive and critical analysis approaches, the research examines peer-reviewed publications (2014–2024) indexed in Scopus, Google Scholar, DOAJ, and Garuda databases, focusing on the PAI-SDGs nexus. Key findings reveal: First, the aspirational alignment of core Islamic values (khalifah, al-’adl, maqasid) with SDGs remains fragmented, lacking holistic operationalization in curricula. Second, significant epistemological tensions (e.g., eschatological vs. worldly orientations; tawhid vs. capitalist growth models) and implementation gaps persist—evidenced by limited teacher capacity, minimal integration in primary education, and a lack of standardized impact assessment tools. Third, the study proposes the PAI-SDGs Nexus framework and Critical Islamic Sustainability Education (CISE) theory as original contributions to bridge these gaps. PAI's contribution to the SDGs remains structurally uncoordinated. The study concludes that a context-sensitive theoretical-operational reconstruction, critical pedagogy-based teacher training, and measurable impact indicators are necessary to bridge the persistent theory-practice discontinuities.